HIGH RATE OF MULTIDRUG RESISTANT BACTERIAL INFECTIONS IN CRITICALLY ILL COVID-19 PATIENTS ADMITTED AT THE PEAK OF PANDEMIC IN A NATIONAL REFERRAL HOSPITAL, KENYA - J. Mutua; A. Musyoki; J. Mwaniki (International Journal of Infectious Diseases, 2023)
Intro: The burden of bacterial infections caused by antimicrobial resistant (AMR) strains in patients infected with viral respiratory tract infections are among the leading cause of death. The role of bacterial infections in pathogenesis of SARS- CoV-2 is not well understood for patients in Kenya and Africa. We evaluated the etiologies, AMR profiles, risk factors and outcomes of bacterial infections in critically ill COVID-19 patients admitted in a tertiary hospital in Kenya Methods: A descriptive cross-sectional study was conducted to between October and December, 2021 in severely ill hospitalized COVID-19 patients at Kenyatta National Hospital Infectious Disease Unit (KNH-IDU). Bacteria identification and antimicrobial susceptibility profiles of the recovered strains were determined using VITEK® COMPACT system. Findings: We sampled 120 PCR confirmed COVID-19 positive patients in this study. The majority of the patients were above 60 years old (43, 35.8%), not vaccinated(98, 81.7%) and had other comorbidities(94, 78.3%). The prevalence of bacterial infection was 44.2%(53/120). K.pneumoniae was the most prevalent cause of bacteremia(42.9%, 3/7). The male patients were three times more likely to acquire bacterial infection patients(aOR=2.61, 95%CI:1.2–5.65,p=0.015). Patients admitted in ICU, prolonged length of hospital stay, non-vaccinated patients and patients aged above 40 years had significantly increased risk of death. All the GPB, except one S. aureus isolate (16.7%,1/6), were 100% resistant to erythromycin. 64.3%,(46/67) of bacteria isolates were MDR and 69.6%,(32/46) of the MDR was attributable to GNB. All isolates of Enterococcus cloacae complex (100%,7/7), Klebsiella pneumonia (100%,16/16), and Escherichia coli (100%,5/5) were MDR. Conclusion: Our study validates that bacterial infections in COVID-19 patients increase disease severity, poor patient outcomes and most bacterial infections are due to MDR organisms.Old age,COVID-19 unvaccination and admission to the critical care unit and lengthy duration of hospital stay have a significantly negative impact on hospitalization outcome. These findings highlight the need for formulating evidence based guidelines for optimal use of antibiotics in management of COVID-19 patients.